Stevia (Stevia rebaudiana B.) yield in the case of different production technologies - Kiss, Annamária; Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2017)
Stevia rebaudiana B. offers a natural alternative of sweetening, potential health promotion plant, and our country shows increased interest about cultivation in Hungary in addition to the neighboring European countries. The agricultural production system installation necessary understanding of the needs of the plant, as well as exploring the agronomic potential. Field experiments were conducted in 2015 with the aim to highlight some of the technological production parameters and correlations between them. We have reviewed the most important agronomic factors, the spacing (50×50 cm and 33×33 cm), ground covering (agro-cloth covered and uncovered/ control), their vegetative growth (first-,second-order branch), herb yield and quality in effect. Based on empirical evidence, that the Hungarian climates also have the opportunity of 3 cuttings during a growing season, besides of early planting, optimal climatic conditions (in October didn’t reduce the daily minimum temperature below 0 °C, after cuttings the maximum interval values remain below 40 °C), and adequate water supply and crop protection facility. The 33×33 cm spacing evaporates more than 50×50 cm spacing, because of the dense population, the continuous canopy less able to breathe, so there are serious chances to the pathogen colonization. Based on the results of our research to the wider 50×50 cm spacing favorable appreciate the stevia optimal progress in terms of qualitative and quantitative parameters of the yield. The stevia yields produced in the Northern Great Plains field cultivation can produce similar results as stevia crop yields in warmer climates, where the primary crops. Our research experience suggest that there is a viable domestic stevia cultivation, developing the necessary technology is still growing further investigation justifies.